2018
DOI: 10.4081/jphia.2018.721
|View full text |Cite
|
Sign up to set email alerts
|

Impact of universal childhood vaccination against hepatitis B in Ghana: A pilot study

Abstract: Hepatitis B virus (HBV) infection is of public health importance worldwide. Vaccination against the infection, especially in early childhood has significantly reduced the public health impact. This pilot study was undertaken in Cape Coast Metropolitan area to assess the impact of the introduction of HBV vaccination in children. A cross-sectional multi-stage cluster sampling of 501 pupils from 30 public and private primary and junior high schools within the Cape Coast metropolis. A questionnaire covering basic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 16 publications
1
11
0
2
Order By: Relevance
“…In the Eastern region, 10.6% prevalence was reported among 1500 pregnant women [6]. It was also lower than other prevalence rates reported in Ghana [15,23,24].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In the Eastern region, 10.6% prevalence was reported among 1500 pregnant women [6]. It was also lower than other prevalence rates reported in Ghana [15,23,24].…”
Section: Discussionmentioning
confidence: 90%
“…However, the introduction of the immunization policy has resulted in fewer infections and lower prevalence among those who were born after the introduction of the HBV immunization policy. To evaluate the impact of the immunization policy on HBV prevalence in the Cape Coast Municipality of the Central Region of Ghana, researchers sampled 501 school children in a pilot study and found that the prevalence of HBcAb was 2.6% and 6.1% among those born after the introduction of the policy and those born prior to the introduction of the policy, respectively [15]. This is a significant difference in the infection rates of those born before the mandatory HBV vaccination policy was introduced and those born after the introduction of the policy.…”
Section: Introductionmentioning
confidence: 99%
“…[ 20 ] In Ghana, the prevalence of anti-HBcAb was 2.6% and 6.1% among pupils delivered after and before the HBV vaccine program introduction, respectively, which shows the effectiveness of the HBV vaccination program. [ 24 ] In Brazil, 29 out of 576 (5.0%) teenagers were reactive for anti-HBcAb. [ 19 ] In Iran, Moghadami et al .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study shows that maternal depression is associated with child stunting, psychological and intellectual development. The lack of psycho-emotional parenting since the pregnancy period weakens 'mother-child' attachment that affects the nutritional status and development of children [49,50]. In nutrition parenting, almost 100% of participants correctly answered the question about the timing of complementary feeding for babies (93.8%), a dietary source of macronutrients rich foods for babies > 6 months old (95.9%), and dietary source of micronutrients rich foods for babies > 6 months old 96.9%.…”
Section: Discussionmentioning
confidence: 99%